Development of a Fluorescent Microfluidic Device Based on Antibody Microarray Read-Out for Therapeutic Drug Monitoring of Acenocoumarol - Salvador, J.-Pablo; Brettschneider, Thomas; Dorrer, Christian; Marco, M.-Pilar (Frontiers in Bioengineering and Biotechnology, 2022)
A high-throughput screening (HTS) immunochemical method for the measurement of plasmatic levels of oral anticoagulants (OAC) is presented. Oral anticoagulant therapy (OAT) such as acenocoumarol (ACL), warfarin (W) and phenprocoumon (PPC), is prescribed to prevent deep vein thrombosis, pulmonary embolism, myocardial infarction and stroke. About 2 % of the population is estimated to be under OAT which expenditures was about $ 144 millions in 2011 . The main problem associated to OAT is related to the narrow therapeutic window of these drugs and to the unpredictable dose-response relationship, thus, is one of the causes for visiting the emergency room at the hospitals. In a previous work, family antibodies were produced for the simultaneous detection of acenocoumarol and warfarin depending on the area of application. It was developed in different format, indirect and direct, either with similar detectabilities and both assays quantifying the oral anticoagulants with high accuracy and reproducibility. We present the implementation of the already developed immunochemical method to a point-of-care (PoC) device to assist on the patient compliance assessment programs. Therefore, a microfluidic system has been developed and merged with the bioreagents to achieve proof-of-principle for a disposable device that could help clinicians monitor patients under OAT. The read-out of the device is based on fluorescent labels that can be easily read with a scanner. The system was tested in order to have a robust and reproducible signal and subsequently an accurate result.